Analisis Volume LNG Ideal untuk Cooling Down Fasilitas LNG Hub - Dhian Nugraha; Harunsyah Harunsyah; Munawar Munawar (Jurnal Teknologi, 2023)
The LNG Receiving Hub facility is an existing facility that has not been used for a long time. In order for this facility can be used again, all equipment and piping systems must first be conditioned to a temperature close to the operational temperature of LNG, which is -160 oC. The purpose of this approach is to determine the theoretical and actual volume of LNG used for the cooling down process of the LNG Hub facility, as well as to compare it with the cooling down process for the regasification facility. An analytical approach is used in this study to determine the ideal amount of LNG needed for cooling down the facility and compare it with the actual amount of LNG that is being used for cooling down the facility. From the results of the analysis, the theoretical LNG volume needed for cooling down the LNG Hub facility is 8,176 m3 and the actual volume is 7,013.6620 m3, while the actual value for cooling down the regasification facility is 11,573.19 m3. The actual volume for the LNG Hub facility is smaller compared to regasification which can be caused by the smaller volume of pipelines and the difference in the cooling down mechanism in both facilities.